Fundamentos para uma análise das dimensões acadêmico-curriculares no contexto do REUNI - Lima, Rochester Santana de (2017)
This dissertation analyzes pedagogical projects of higher education graduation courses created in the occasion of Reuni, in the Centro de Ciências Jurídicas e Econômicas of the Espírito Santo Federal University. It is documental research, using the methodology of content analysis towards an approximation to the Political Pedagogical Projects of graduation courses, and this task was achieved through the approximation between structural changes in capitalism, from the 1970s, and the emergency of speeches and principles of the human capital theory, knowledge society and pedagogy of skills. Increasingly strengthened in the structural crisis scenario, these principles characterized nation’s development perspectives through educational politics, usually linked to focused, individual and private notions of the subjects in the educational process, as well of its institutions and the government role in the defining their education policies, and among them, their policies towards higher education. In this context, the process of counter-reform of higher education in Brazil was forged over aspects of its particularity regarding the constitution of brazilian economic elite and capitalism in this country, combined with its condition of dependence, expressed by the outstanding influence of multilateral organizations in defining economic and social politics assumed by different governments. The proposals of expansion/restructuration of federal universities in Brazil, however, tend to express, on higher education courses, aspects related to mercadization of educational process, and in which the pedagogical projects of the courses have fundamental role.